Monitoring performance of hydroelectric power plants - Vaz, Clara B. (2014)
This study develops a methodology to provide insights regarding the efficiency and productivity of the hydroelectric power plants of an European player in the energy sector throughout the operation stage. DEA is used to measure the efficiency of utilities in generating electrical energy from the resources available and exogenous variables. This analysis enables the identification of the best practices of power plants which lead to improved performance. The Malmquist index, complemented with bootstrapping, is used to measure the changes in plants productivity between in the last years.